2021
DOI: 10.1177/07334648211023251
|View full text |Cite
|
Sign up to set email alerts
|

White and Black Differences in Perceived Access to Health and Community Services and Self-Rated Health in an Age-Friendly Community Assessment

Abstract: Objectives: This study sought to identify the race differences in perceived access to health and community services and self-rated health (SRH) among White and Black older adult participants of an age-friendly community assessment. Methods: Responses ( n = 313) to a baseline assessment of Columbus, Ohio, residents aged ≥50 years were analyzed. Results: Significant differences were found between White and Black older adults regarding SRH, with Black older adults reporting lower SRH. Black older adults reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Controls for income and race would be helpful in this regard. Racial segregation, for example, could possibly account for the greatest mismatches between livability scores and concentrations of older adults, which also has implications for the prevalence and persistence of racial disparities in access to health and community services among older adults (Krok-Schoen et al, 2021). As decades of systematic and institutional discrimination in housing such as “redlining” and its resulting effects (e.g., disinvestment in urban areas) (Galster, 1990; Massey & Denton, 1998) significantly contributed to the establishment of a dual housing market system (Stearns & Logan, 1986), the white majority was incentivized to settle in suburban locations, while non-white minorities were coerced into settling in urban areas (Crowder, 2000; Dawkins, 2016; Flippen, 2001; South & Crowder, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Controls for income and race would be helpful in this regard. Racial segregation, for example, could possibly account for the greatest mismatches between livability scores and concentrations of older adults, which also has implications for the prevalence and persistence of racial disparities in access to health and community services among older adults (Krok-Schoen et al, 2021). As decades of systematic and institutional discrimination in housing such as “redlining” and its resulting effects (e.g., disinvestment in urban areas) (Galster, 1990; Massey & Denton, 1998) significantly contributed to the establishment of a dual housing market system (Stearns & Logan, 1986), the white majority was incentivized to settle in suburban locations, while non-white minorities were coerced into settling in urban areas (Crowder, 2000; Dawkins, 2016; Flippen, 2001; South & Crowder, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Tetyana et al examined the ethnic disparities in the relationship between the use of HCBSs and SRH among American older adults [ 25 ]. Jessica et al demonstrated a correlation between perceived access to HCBSs and SRH in older adults living in the age-friendly community [ 26 ]. Yang et al have demonstrated the role of different types of HCBSs in SRH among general older adults using data from Shaanxi Province, China [ 27 ].…”
Section: Introductionmentioning
confidence: 99%